(3TQM CQLhRI GHf SjfG aj GdWHs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdefYe HMjGI GdfaS hUMI GdCLSGe , hGdTGai ef GdCOhGA GdeYVdI hGdCSbGe s
(3BNQgG (B:s
(3eHJhQI GdBNQ , JfJgi CKfGA GdcdGe Ydi YdGL GdNdY ai GdYXe , hTQM bhd GdQFjS hGdNdY WHg HeG jeOg MJi Edi ehVYg jQOg s
(3fSNI QGHYIs
(3GdhQbI GdChdi HNW eZQHi eZGjQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs